Bridging the Policy and Implementation Gap: Regional Bureaucracy and the Governance of Smallholder Oil Palm Plantations - Ikhsan Ikhsan; Vellayati Hajad; Ahmad Harakan; Deni Setiawan; Safril Yanda (LPPM Universitas PGRI Sumatera Barat, 2026)
This study examines the persistent gap between centrally mandated sustainability policies and their implementation in smallholder oil palm plantations in Indonesia, with a focus on the role of regional bureaucracies. It aims to analyze how local bureaucratic actors bridge the disconnect between policy design and on-the-ground realities, particularly in the context of Indonesian Sustainable Palm Oil (ISPO) standards and related programs. Grounded in the Street-Level Bureaucracy framework, this research adopts a qualitative case study approach in West Aceh Regency. Data were collected through in-depth interviews with smallholder farmers, field officers, and government officials, supported by participant observation and document analysis, and analyzed using thematic analysis. The findings reveal that field-level bureaucrats function as active policy actors who interpret, adapt, and operationalize central regulations through discretionary practices, improvisation, and context-sensitive strategies. These adaptive mechanisms—such as simplifying procedures, prioritizing services, and engaging in social negotiation—are crucial in aligning formal policy requirements with local socio-economic conditions. However, implementation is significantly constrained by structural limitations, including inadequate human resources, limited infrastructure, insufficient funding, and socio-political pressures such as elite intervention and high central performance targets. The study concludes that the effectiveness of smallholder oil palm governance is highly dependent on the adaptive capacity of regional bureaucracies. Strengthening institutional flexibility, bureaucratic capacity, and multi-level coordination is essential to enhance policy outcomes. This research contributes to the literature by demonstrating how bureaucratic discretion, structural constraints, and local political dynamics interact in shaping policy implementation, offering both theoretical and practical insights for more inclusive and sustainable agricultural governance.